Laser-Assisted Lip Repositioning Surgery: A Modification to The Conventional Technique: Laser-Assisted Lip Repositioning Surgery. - Blanco Florez, Pilar RocÃo; Alvis Guzmán, Jessica; Orozco Páez, Jennifer (Journal of Lasers in Medical Sciences, 2022)
Introduction: The lip repositioning surgical technique arose with the objective of correcting and harmonizing the act of smiling. Since the conventional technique was published, some modifications of the technique have been proposed in order to counteract postoperative recurrence and to achieve the best esthetic appearance of the smile. The objective of this paper was to describe the laser-assisted lip repositioning technique (laser-assisted LRS) with a 940nm diode laser and 2780nm Er, Cr: YSGG, as a modification to the conventional lip repositioning technique, for the treatment of a gummy smile. Case Report: The proposed technique consists in achieving the descent of the upper lip by removing the intraoral mucosal band through the laser peeling of the oral mucosa, preserving the connective tissue intact for healing by secondary intention. The technique was implemented in two patients with a diagnosis of a gummy smile caused by a short and hyperactive upper lip; the healing process was satisfactory, and there was no bleeding or postoperative edema. Postoperative controls were performed at 3 and 10 months, and no recurrence was found. Conclusion: the 940nm Diode laser or 2780nm Er, Cr: YSGG laser-assisted lip repositioning the technique described here is less invasive than that performed with a conventional scalpel, offers aesthetic results, lower risk of infection, and recurrence of the gummy smile in the long term. Doi:10.34172/jlms.2022.22